Israel and Palestine : alternative perspectives on statehood - Ehrenberg, John, 1944-; Peled, Yoav (Rowman & Littlefield Education, 2016)
This book is designed to introduce American readers to the terms of the discussion of a two-state solution. It features essays by well-known Israeli academics, both Jewish and Palestinian, as well as contributions from non-Israeli citizen Palestinian, and American scholars. It is the first to bring together a wide-range of views and perspectives by influential scholars from various disciplines as well as from activists to bear on a very topical subject with international ramifications.
Keywords: Arab-Israeli conflict -- 1993- -- Peace.; Israel -- Politics and government -- 1993-; Palestinian Arabs -- Politics and government -- 1993-; Palestine question (1948-); Conflit israélo-arabe -- 1993- -- Paix.; Israël -- Politique et gouvernement -- 1993-; Palestiniens -- Politique et gouvernement -- 1993-; HISTORY -- Middle East -- General.; Arab-Israeli conflict -- Peace; Palestinian Arabs -- Politics and government; Politics and government; Israel; Since 1993; Electronic book.